دور مناخ الاستثمار في جذب الاستثمار الاجنبي المباشر في الجزائر - مباركة, لجدل الصيد; نجود, عرعار (University of eloued جامعة الوادي, 2021)
"من أجل استقطاب الاستثمار الاجنبي المباشر تسعى الدول الى توفير مناخ الاستثماري مناسب في ضل التحديات والتطورات التي تعرفها الساحة الدولية، في ضل هاته التطورات قامت الجزائر بعدة اصلاحات اقتصاديه وتحفيزات، إضافة إلى العديد من القوانين والتشريعات، جاءت هذه الدراسة لتهدف إلى توضيح واقع المناخ الاستثماري في الجزائر وأثره على الاستثمار الأجنبي المباشر في الجزائر في الفترة الممتدة بين (2000-2016) ، وتم اتباع المنهج الوصفي والتحليلي، في الدارسة والتي أبرزت عدة نتائج من أهمها أن النجاح في جذب الاستثمار الأجنبي المباشر مرتبط بتوفير ظروف وشروط اقتصادية وامنيه وسياسية ملائمة، ورغم الجهود التي بذلتها الجزائر في جذب الاستثمار الأجنبي المباشر إلا أنها مازالت بعيدة نوع ما عن ما هو متوقع. ""In order to attract foreign direct investment, countries seek to provide a suitable investment climate in light of the challenges and der international arena, In light of these developments, Algeria undertook several economic reforms and incentives, in addition to many laws and legislations, this study aimed to clarify the reality of the investment climate in Algeria and its impact on foreign direct investment in Algeria during the period between (2000- 2016), the descriptive and analytical approach was followed, in the study, which highlighted several results, the most important of which is that success in attracting foreign direct investment is linked to providing appropriate economic, security and political conditions and conditions, despite the efforts made by Algeria to attract foreign direct investment, it is still somewhat far from what is expected. "
مذكرة ماستر مالية وتجارة دولية
Keywords: الاستثمار الاجنبي، الاستثمار الاجنبي المباشر، المناخ الاستثماري، البيئة الاقتصادية.; foreign investment, foreign direct investment, investment climate, economic environment.